2007
DOI: 10.1149/1.2792322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Defects in Silicon Substrate on Flash Memory Characteristics

Abstract: Floating-gate-type Flash memories are fabricated on Czochralski ͑CZ͒ silicon wafers. A large amount of residual misalignment in reticle shots at the photolithography process step and the programing failure are observed in the low oxygen concentration wafer. To investigate the origin of misalignment and programing failure, X-ray topography, optical microscope observation followed by preferential etching and laser scattering tomography observation are performed. Slip propagation from wafer edge to wafer center a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In particular, for semiconductor devices that require complicated structural enhancements such as scaling and three-dimensional chip integration, new technology for controlling oxygen precipitates will gain more significance, specifically because endurance against the stress induced in Si wafers during device fabrication is becoming increasingly crucial. [4][5][6] The behavior of oxygen precipitates in Cz-Si crystals is closely related to point defects such as vacancies and interstitial Si atoms. [7][8][9] Vacancies promote the formation of oxygen precipitates because their nucleus is formed as a complex between oxygen atoms (O) and vacancies (Va); for instance, in the form of O 2 Va.…”
mentioning
confidence: 99%
“…In particular, for semiconductor devices that require complicated structural enhancements such as scaling and three-dimensional chip integration, new technology for controlling oxygen precipitates will gain more significance, specifically because endurance against the stress induced in Si wafers during device fabrication is becoming increasingly crucial. [4][5][6] The behavior of oxygen precipitates in Cz-Si crystals is closely related to point defects such as vacancies and interstitial Si atoms. [7][8][9] Vacancies promote the formation of oxygen precipitates because their nucleus is formed as a complex between oxygen atoms (O) and vacancies (Va); for instance, in the form of O 2 Va.…”
mentioning
confidence: 99%
“…However, Nitecki et al and Hirano et al have discovered to occasionally cause punched-out dislocations that are harmful to the mechanical strength of CZ-Si wafers. [135,136] Moreover, if oxygen precipitates enter into the active region, it will raise the leakage current of device. Zeng et al have shown stress field interactions between precipitates and dislocations-which are more effective for platelet oxygen precipitates and perhaps less effective for polyhedral oxygen precipitates-frequently and effectively causing dislocation locking in CZ-Si.…”
Section: Nfz-simentioning
confidence: 99%
“…The defect denuded zone and the microdefect density in the bulk defect zone should be tailored with respect to the device process. High densities of oxygen precipitates can cause plastic deformation of silicon wafers which results in overlay problems in photolithography steps [8,9]. Therefore, density and size of oxygen precipitates need to be carefully tuned to efficiently getter the metals without causing geometry problems.…”
Section: Introductionmentioning
confidence: 99%